Active Experiments Beyond the Earth: Plasma Effects of Sounding Radar Operations in the Ionospheres of Venus, Mars, and the Jovian System - Voshchepynets, Andrii; Barabash, Stas; Holmstrom, Mats; Frahm, Rudy A. (Frontiers in Astronomy and Space Sciences, 2019)
The operation of powerful satellite- and rocket-born sounding radars is often accompanied by a heating/acceleration of the local electrons and ions. Intense fluxes of sounder accelerated particles were detected in Earth's ionosphere when the frequency of the radar transmitter was close to one of the fundamental plasma resonances: harmonic of the electron-cyclotron frequency, plasma, or upper-hybrid frequencies. Recently it was found that running a sounder in the ionosphere of the non-magnetized Mars results in similar effects. Ion and electron sensors of the ASPERA-3 experiment (Analyzer of Space Plasma and Energetic neutral Atoms) onboard the Mars Express spacecraft discovered acceleration of the local ionospheric ions and electrons from thermal threshold energies to 100's of eV during the active sounding phase of the onboard sounder. ESA and NASA missions being studied or under development to Jupiter (JUICE- JUpiter ICy moon Explorer) in 2022, Europa Clipper in 2023 and to Venus (EnVision) in 2032 and ISRO Venus obiter in 2023 will also carry powerful sounding radars. The purpose of this study is to investigate what mechanisms can cause acceleration of the plasma particles during operations of the proposed sounding radars in the Jovian system and Venusian ionosphere. Using the results of the previous studies and characteristics of the proposed sounding radars onboard JUICE, Europa Clipper, EnVision, and ISRO Venus Obiter, we define the optimal conditions for observations of sounder accelerated particles, depending on the local conditions, such as plasma density, composition, and intensity of the magnetic field. The EnVision and ISRO Venus Obiter radar operations are expected to result in the most pronounced acceleration of ions and electrons, an effect that can be used to improve the local plasma diagnostics.